Liturgy as a Factor in the Preservation of the Lithuanian and Prussian Ethnic Identity in the Duchy of Prussia in the Sixteenth Century - Petkūnas, Darius (Senoji Lietuvos literatūra, 2018)
The introduction of divine services in the language of the people was considered an important task in the Reformation. Implementation of this programme in Prussia began in 1524 when the bishop of Sambia ordered that henceforth baptisms should be conducted in German. The 1525 order of the Prussian church called for divine services in the language of the people and indicated specifically which parts of the service were to remain in Latin and which were to be in German.The German language was already an official language of the land but the Reformation now provided an opportunity for other ethnic groups in Prussia to legitimize their own tongues as official and legitimate languages in the realm. This could only be achieved if these languages were used in the Lutheran Mass and other services, that is, they had to become the languages of the church. Such a course was encouraged by the Sambian and Pomesanian bishops and the ducal court. The 1544 Prussian agenda specifically ordered that catechetical sermons were to be preached to ‘the Lithuanians and other non-Germans’ in their own tongue.The first to translate the 1544 Prussian agenda into their own tongue were the Masurian Poles. The Lithuanians also took advantage of the opportunity to translate the divine services into their native language. Almost all of the works prepared by Martynas Mažvydas and Baltramiejus Vilentas were liturgical in nature. The 1547 and 1579 catechisms included not only catechetical instruction but also liturgical service material. The 1547 book included liturgical hymns, and the translation of Luther’s Enchiridion by Vilentas in 1579 included orders for marriage and baptism. In that same year Vilentas published the Euangelias bei Epistolas (Gospels and Epistles), a compilation of Sunday and feast day pericopes to be read from the altar during the Mass, Matins, and Vespers. As the result of all this activity, the Lithuanian language became a liturgical language, the language of the Lithuanian church officially recognized throughout the Duchy of Prussia. It is significant to note that these liturgical materials were prepared not by men of the Lithuanian ethnic group in Prussia, but by the graduates of Königsberg University from the Grand Duchy of Lithuania – the nobles who had been forced to leave Lithuania because they were Lutherans.The ethnic Prussians were unable to make effective use of their opportunity to legitimize their language. The forms for baptism and marriage were indeed translated into ethnic Prussian and were included in the 1561 Prussian catechism. However, there is no evidence indicating that parts of the Mass, or Matins and Vespers, or hymns were said or sung in the Prussian tongue. Duke Albrecht provided scholarships for ethnic Prussians to study at the University of Königsberg, but the Prussians were no longer able to raise up a native clergy to prepare the most important liturgical services in their own tongue. As a result, the Mass and other divine services were celebrated in Prussian congregations in the German tongue, and this only accelerated the already deep decline of the Prussian language. It soon became a dead language.
Keywords: Lutheran Church; Liturgy; Mass; agenda; Prussian language